2017
DOI: 10.1016/j.dib.2016.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of total, oligomeric alpha-synuclein and hemoglobin levels in plasma in Parkinson׳s disease

Abstract: This data article presents a dataset of total, oligomeric alpha-synuclein and hemoglobin levels in plasma of drug-naïve PD patients and controls. This is the first attempt to assess the effect of hemolysis rate on oligomeric alpha-synuclein levels in peripheral plasma. The data are associated with the research article “Oligomeric alpha-synuclein and glucocerebrosidase activity levels in GBA-associated Parkinson׳s disease” (Pchelina et al., 2016) [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…As lumbar puncture is an invasive procedure, differences in α-syn levels have been explored in more accessible biofluids, like blood. In this regard, several studies have showed contradictory results, some authors finding increased levels of plasma or serum α-syn in PD patients [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], whereas others found no changes [22][23][24][25][26][27][28][29][30][31][32][33][34][35] or even reduced levels [36,37]. The analysis of different proteoforms of α-syn, like oligomeric (o-syn) and phosphorylated (p-syn) forms, has raised equally variable results [13,22,26,28,32,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…As lumbar puncture is an invasive procedure, differences in α-syn levels have been explored in more accessible biofluids, like blood. In this regard, several studies have showed contradictory results, some authors finding increased levels of plasma or serum α-syn in PD patients [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], whereas others found no changes [22][23][24][25][26][27][28][29][30][31][32][33][34][35] or even reduced levels [36,37]. The analysis of different proteoforms of α-syn, like oligomeric (o-syn) and phosphorylated (p-syn) forms, has raised equally variable results [13,22,26,28,32,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study, the combination of total α‐Syn, proteinase‐K resistant (PK res ) α‐syn and phospho‐Serine 129 α‐Syn could differentiate HC and presenting motor symptoms without dementia (PD‐M) with an AU of 0.81, while levels of oxidised α‐syn did not significantly differ among the groups (Abd Elhadi et al, 2019). Oligomeric α‐syn levels were also elevated in serum (Williams et al, 2016), plasma (Ding et al, 2017) and RBC (Wang et al, 2015) of PD patients, although this elevation was not significant during the early stage of PD (Emelyanov et al, 2017). The combination of oligomeric α‐syn, total α‐syn and amyloid β peptide 1–42 (Aβ42) achieved high diagnostic accuracy (Daniele et al, 2018).…”
Section: α‐Syn Inescapable Subjectmentioning
confidence: 99%
“…Egindako ikerlanetan lortutako emaitzen arteko desberdintasunak azaldu ditzake horrek. Parkinsona duten pazienteetan α-sinukleina totala plasman neurtzean eta kontrolekin alderatzean egoera desberdinak deskribatu dira: igoera [54][55][56][57][58][59][60][61][62], murrizketa [63] eta aldaketarik eza [64][65][66][67][68].…”
Section: Alfa-sinukleinaren Mailak Odol-plasmanunclassified
“…Horrela, bi ikerlanen arabera, proteoforma horren maila handiagoa da Parkinsona duten pazienteen plasman kontrol osasuntsuen plasman baino [69,70]. Emelyanov-ek eta haren kolaboratzaileek, ordea, Parkinson gaixotasunean maila txikiagoan aurkitzen dute [65], eta beste ikerlan batek ez du aldaketarik deskribatzen [63]. Azkenik, badirudi α-sinukleina fosforilatuaren maila handituta dagoela Parkinsona duten pazienteen plasman.…”
Section: Alfa-sinukleinaren Mailak Odol-plasmanunclassified